The Strategy to Optimize the Role of Government Internal Supervisory Apparatus (APIP) in Procurement Fraud Risk Management in Industry 4.0 - Kamal, Mustofa; Elim, John (Badan Pemeriksa Keuangan Republik Indonesia, 2021)
Many challenges confront the efforts to build procurement fraud risk management in Industry 4.0. This study aims to assess the risk of procurement fraud in industry 4.0 and disclose strategies to optimize the role of internal auditors in mitigating these risks. The mixed-method has been conducted with data on procurement fraud risks generally accepted by government agencies. A survey involving 140 respondents and interviews with five experts have been completed. The risk assessment in the research findings involved seven procurement fraud risks, with